Influence of Fine Glass Aggregate On Cement Mortar (International Journal of Engineering and Computer Science, 2014)
In order to make concrete industry sustainable, the use of waste materials in place of natural resources is one of the best alternatives. In this paper, an investigation was conducted to study on the viability of using waste glass as an alternative material applied as partial replacement of fine aggregates in manufacturing fresh mortar. Fine aggregates were replaced by waste glass aggregate as 10%, 20% and 30% by weight for mortar mix1:3. The mortar specimens were tested for compressive strength at 1, 3, 7, 28 days of age and the results obtained were compared with those of control block of mortar. The test results shows that the replacement of fine aggregate by fine glass at level of 20% by weight has a significant effect on the compressive strength of the mortar blocks as compared with the control sample because of pozzolanic nature of fine glass.